Microscopic characteristic of biological iron sulfide composites during the generation process and the association with treatment effect on heavy metal wastewater - Yang, Yang (Water science and technology : a journal of the International Association on Water Pollution Research, 2014)
Heavy metal pollution is a serious environmental concern worldwide, resulting in both environmental and human harm. Recently, studies have shown that environmental biotechnologies based on sulfate reduction offer a potential for removal of toxic heavy metals. Biological iron sulfide composites are iron sulfide compounds generated in situ by sulfate-reducing bacteria. In this study, microscopic morphological changes during the composites' generation process were studied, and the effect of biological iron sulfide composites in different generation phases on treatment of heavy metal wastewater was investigated to establish the correlation between macro-effect and micro-properties. The results revealed that the generation process of biological iron sulfide composites occurs in three phases: the formation phase, stationary phase, and agglomeration phase. The stationary phase can be divided into a pre-stationary phase and post-stationary phase. It was found that the best treatment time for Cr(6+) is in the pre-stationary phase, while the best treatment time for Cu(2+)and Cd(2+) is in the post-stationary phase. The results of this study further prove the benefits of treatment of heavy metal wastewater using biological sulfide composites and provide theoretical guidance in practical applications